STUDI EMPIRIS DAMPAK FISKAL BADAN LAYANAN UMUM BIDANG PENDIDIKAN DAN KESEHATAN - Dinarjito, Agung (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2018)
One of the reforms of State Finance management reflected in the package of the State Finance Act is by allowing a flexible form of government work units known as the Public Service Agency. Flexibility in the management of finance has greatly increased the number of public service agencies. Under the prevailing rules, increasing the number of Public Service Agency will have an impact on the fiscal due to the Government should provide additional budgets to meet mandatory spending. This paper aims to calculate the value of the fiscal impact on revenues and expenditures of the Public Service Agency in the Education and Health field from 2011 through 2015. The research method used is a descriptive quantitative method using mathematical equiation to calculate and explain the fiscal impact. The results of the research indicate that the fiscal impacts resulting from BLU's revenues on education and health in 2015 amounted to 37.18% of BLU revenue, while the fiscal impact of BLU spending on education in 2015 amounted to 5% of BLU spending and 20% for BLU on Health.Â From the results of the study, it can be concluded that the BLU in the Education and Health sector will provide a fiscal impact for government from the income generated and from BLU expenditure.Â